Development of Independent Basic Training Model Based on Early Childhood Teacher Competency in Kubu Raya Regency - Muhammad Yusuf; M. Syukri; Wahyudi Wahyudi (STKIP Singkawang, 2018)
In carrying out its duties and functions, early childhood teachers must meet the qualifications and competencies required in accordance with PERMENDIKBUD no. 137 of 2014 on the National Standards of Early Childhood Education. But in fact of early childhood teachers have varying variations in qualification and competence. Still found educators who are elementary education, but so many educators who have secondary education (high school or vocational school) and very few who have diploma and graduate education, although not relevant/appropriate with the field of education of early childhood. It is necessary to design a basic level tiered training that can be used by the organizers that are effective and efficient to overcome these problems. The purpose of this study is to develop the basic training model based on the competence of early childhood teachers in Kubu Raya. This study includes a type of research development with reference to the opinion of Borg & Gall. Products developed based on preliminary research are basic competency-based training and training. The test subject in this research is subject of expert, that is expert in the field of Early Childhood Education training, as well as subject of the basic training participants as potential users of the product. The determination of participant subjects for operational field test amounted to 19 teachers of Kubu Raya. Data collection techniques were conducted by questionnaire. The questionnaire is used to assess the training design that is developed in terms of needs analysis, the preparation of training programs, recruitment of participants, preparing training plans, trainers, training facilities, training schedules and administration. Data were analyzed descriptively, quantitatively and qualitatively. The results showed that, on field trial of basic education model based on the competence of early childhood teachers in Kubu Raya included in the effective category. The result of calculation of posttest result distribution shows the dominant calculation is effective as many as 10 people or 53%. Thus, the basic training model based on the competence of the development result is feasible to be used by the basic training provider for teachers.